Investigating the effect of solid powder particle size on the turbulent multi-phase flow in pipelines - Mohammad Razif, Abdul Rahman (2011)
Drag reduction has been first reported by Tom in 1949 due to the effect produced by polymer addition in fluids.The problem of pumping power losses in pipeline flow cause the phenomenon drag reduction was introduced.Drag reduction be defined as the increase in pumpability of a fluid caused by the addition of small amounts of another substance to the fluid.In this present study,aluminium and carbon was investigated as drag reducing agents in two phase flow and the flow tested were conducted using water as the carrying liquid.The variables that take part are flowrate, concentration of suspended solid particle,size of suspended solid particle,type of suspended solid particle and pipe length(testing point distance).The variable is manipulated according to the subject studied.The experimental works is conducted in a closed loop of turbulence water flowing system. The obtained data was analyzed and the result show that, in the effect of types of particles,carbon powder produce the higher percentage of drag reduction compared to aluminium powder.That means carbon is better DRA compared to aluminium.Both particles with size 200µm produce higher percentage of drag reduction compared to the particles with size 400µm.The result also show that the addition of 700ppm of particle give the higher percentage of drag reduction for both types of particles. This experiment also show that higher percentage of drag reduction is achieved when the Reynolds number(Re)is 45950 and at 2m pipe length.The maximum percentage of drag reduction (Dr%) is 84% achieved from aluminium 400µm with 700ppm at 2m pipe length.The result also shows that there is instability in the percentage of drag reduction(Dr%) for all the variables. Carbon particle were found possible to behave as a DRA but for the aluminium particles,there are no clear explanation about the results.